2007
DOI: 10.1158/0008-5472.can-06-3087
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 Promotes Invasion-Related Properties in Human Colorectal Carcinoma Cells

Abstract: CXCL10 was recently shown to exert antimalignancy functions by influencing the tumor microenvironment. Here, we have taken a different approach, investigating the effects of CXCL10 directly on tumor-promoting functions in colorectal carcinoma (CRC) cells. CXCL10 expression was detected in preferred metastatic sites of CRC (liver, lungs, and lymph nodes), and its CXCR3 receptor was expressed by eight CRC cell lines (detected: reverse transcription-PCR and/or flow cytometry). Detailed analysis was done on two ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
152
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 49 publications
(77 reference statements)
7
152
0
1
Order By: Relevance
“…CXCR3 has been identified in biopsies of ovarian and renal cell carcinomas (18,19). Two laboratories have described the expression of CXCR3 in colon cancer (22,24) and observed CXCR3 both in the cytoplasm and plasma membrane of malignant, but not normal, colonic epithelium. CXCR3 expression was strongly correlated with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR3 has been identified in biopsies of ovarian and renal cell carcinomas (18,19). Two laboratories have described the expression of CXCR3 in colon cancer (22,24) and observed CXCR3 both in the cytoplasm and plasma membrane of malignant, but not normal, colonic epithelium. CXCR3 expression was strongly correlated with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The data on the effects of CXCR3 ligands on tumor cell proliferation are contradictory: In some human tumor cells, ligand induces tumor cell proliferation (6,17,22), and in other cells, ligand has no effect on cell growth (24). Some of these differences are likely attributable to the expression of CXCR3 splice variants in different cells (24,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][13][14][15] In CRC, it was reported that CXCR3 expression is upregulated in metastatic colon cancer cells, but not in their primary lesions, and that the CXCL10/CXCR3 axis…”
mentioning
confidence: 99%
“…3 CRC cells have been found to express the chemokine receptors CXCR4 and CXCR3. [4][5][6][7][8][9] Chemokine receptor CXCR4 is the first identified chemokine receptor to play a critical role in determining the metastatic destination of breast cancer to the bone and lungs where its ligand CXCL12 is abundant. 10,11 It was also reported that metastasis of mouse colon cancer cell line CT-26 to the liver and lungs was greatly reduced when CXCR4 function was blocked.…”
mentioning
confidence: 99%